LncRNA-BLACAT1 Facilitates Proliferation, Migration and Aerobic Glycolysis of Pancreatic Cancer Cells by Repressing CDKN1C via EZH2-Induced H3K27me3 - Zhou, Xin; Gao, Wei; Hua, Huanhuan; Ji, Zhimin (Frontiers in Oncology, 2020)
Objective: To investigate the role of lncRNA-BLACAT1 in promoting H3K27 trimethylation of CDKN1C gene by recruiting EZH2 to regulate CCNE on glycolysis and mitochondrial oxidative phosphorylation of pancreatic cancer (PC) cells. Methods: Following bioinformatic prediction, EZH2 and BLACAT1 in PC cells were interfered, and cells proliferation, migration and invasion in each group were detected. Western Blotting detected the expression of key proteins of mitochondrial complex. The sub-cellular localization of BLACAT1 was tested, followed by testing the binding of CDKN1C and BLACAT1 with EZH2, followed by in vivo verification. Results: Based on bioinformatic prediction, EZH2 and BLACAT1 were highly expressed in PC, while CDKN1C was lowly expressed (all P<0.05). Interference with EZH2 and BLACAT1 inhibited cell proliferation, migration and aerobic glycolysis, and promoted mitochondrial oxidative phosphorylation (all P<0.05). BLACAT1 promoted H3K27 trimethylation of CDKN1C through recruiting EZH2 (all P<0.05). in vivo results showed that BLACAT1 interference inhibited tumor formation (all P<0.05). Conclusion: Interference with BLACAT1 inhibits H3K27 trimethylation of CDKN1C gene by blocking EZH2 recruitment to promote CDKN1C expression and inhibit CCNE expression, thus suppressing PC cell proliferation, migration and aerobic glycolysis, and promoting mitochondrial oxidative phosphorylation.